Case report: Amphiphysin-IgG autoimmunity: a paraneoplastic presentation of appendiceal goblet cell carcinoma - Lin, Jingfang; Yu, Tianping; Wang, Minjin; Wang, Jierui; Li, Jinmei (Frontiers in Immunology, 2023)
Background Appendiceal goblet cell carcinoma (aGCC) is a rare neoplasm with mixed endocrine and exocrine features. No paraneoplastic neurological syndromes or autoantibodies have been identified in cases of aGCC or even appendiceal tumors. Amphiphysin-immunoglobulin G (IgG) autoimmunity was first described in stiff-person syndrome with breast cancer. We firstly described the clinical course and pathological findings of a patient with aGCC-associated amphiphysin-IgG autoimmunity. Case presentation A 54-year-old man who developed aGCC was admitted for acute disturbance of consciousness, psychiatric symptoms, cognitive impairment, seizure and hypotension. Amphiphysin-IgG was detected in the patient’s serum and CSF by immunoblotting and tissue-based indirect immunofluorescence assay confirming the diagnosis of definite paraneoplastic amphiphysin-IgG-positive encephalitis. Histopathology revealed amphiphysin protein expression and accompanying immune cell infiltration (predominantly CD20+ B cells, CD3+ and CD8+ T cells) within the tumor tissue, suggesting a possible paraneoplastic origin of amphiphysin-associated paraneoplastic neurological syndromes (PNSs) in this case. Although the patient’s symptoms resolved after high-dose corticosteroid therapy, he experienced recurrence 6 months later, manifesting as paraneoplastic cerebellar dysfunction. Despite treatment with IV cyclophosphamide and oral mycophenolate mofetil, no improvement was noted. Conclusions This case suggests that aGCC may trigger amphiphysin-IgG autoimmunity.